Functional characteristics of the elderly of the National Police of Colombia - Castillo Daza , Carlos Alberto (2025)
Introduction: Aging as a characteristic of the elderly is a universal and continuous psychophysiological process that brings with it a decrease in functional capacity in subjects. Objective: To determine the functional characteristics of older adults in retirement from the National Police of Colombia Method: Cross-sectional descriptive and exploratory study where 190 subjects of both sexes with an average age of 67 ± 12 years participated in the study. Body composition was evaluated through tetrapolar bioimpedance and functional capacity through the Senior Fitness Test battery. Results: More than 60% of the subjects are overweight and obese. On the other hand, higher values ​​were found in the functional capacity evaluated through the six tests that make up the test battery, with respect to the reference values. Additionally, a backward linear regression model is proposed when analyzing the relationship of body mass index (BMI) with the Senior Fitness Test. Conclusions: The participation of the elderly in institutionalized physical activity programs is essential, in order to reduce the levels of overweight and obesity, in turn, the risk that this condition carries for the development of chronic diseases of age.